2020
DOI: 10.3389/fpls.2020.579019
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Lipid Droplets in Plants and Algae—Right Time, Many Paths, One Goal

Abstract: In eukaryotic cells, lipids in the form of triacylglycerols (TAGs) are the major reservoir of cellular carbon and energy. These TAGs are packed into specialized organelles called lipid droplets (LDs). They can be found in most, if not all, types of cells, from bacteria to human. Recent data suggest that rather than being simple storage organelles, LDs are very dynamic structures at the center of cellular metabolism. This is also true in plants and algae, where LDs have been implicated in many processes includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 188 publications
(280 reference statements)
0
43
0
Order By: Relevance
“…Lipid droplets can also be degraded by the autophagy-related lipophagy process ( Zienkiewicz and Zienkiewicz, 2020 ). It has recently been shown that the major LD surface protein of the eustigmatophyte Nannochloropsis oceanica interacts with the hallmark autophagy protein ATG8 during the autophagic catabolism of LDs ( Zienkiewicz et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid droplets can also be degraded by the autophagy-related lipophagy process ( Zienkiewicz and Zienkiewicz, 2020 ). It has recently been shown that the major LD surface protein of the eustigmatophyte Nannochloropsis oceanica interacts with the hallmark autophagy protein ATG8 during the autophagic catabolism of LDs ( Zienkiewicz et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to serving as a reservoir for neutral lipids, LD is believed to play roles in many biological processes, such as lipid homeostasis, signaling, membrane trafficking, etc. [ 213 215 ]. Proteomic studies of LD fraction, which help understand LD biology and lipid metabolism, have been conducted for many algae including C. reinhardtii [ 216 218 ], N. oceanica [ 219 ], Fistulifera sp.…”
Section: Lipid Metabolism In C Zofingiensismentioning
confidence: 99%
“…Shown in Supplementary Dataset 3 are the summed LFQ and enrichment values for all detected proteins at different subcellular localizations based on PPDB (Sun et al, 2009;Ischebeck et al, 2020), including proteins annotated to be localized at LDs, which were the most enriched in the LD fractions, as expected. Among the other notable groups of proteins enriched in the LD fractions were those annotated to be localized to tonoplasts or vacuoles (Supplementary Dataset 3), which might reflect the LD-vacuole interactions that are proposed to occur during autophagic degradation of LDs in plants (Ischebeck et al, 2020;Zienkiewicz and Zienkiewicz, 2020), as well as proteins localized to lipid-storing plastoglobuli, which, like cytosolic LDs, are known to be upregulated during plant stress (Rottet et al, 2015;Lundquist et al, 2020).…”
Section: Erd7 Is Enriched With Lds Isolated From Drought-stressed Aramentioning
confidence: 99%